2011
DOI: 10.1177/1753944710396538
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B and Tanshinone IIA attenuate myocardial ischemia injury in mice by NO production through multiple pathways

Abstract: These findings suggest that both Sal B and Tan IIA have cardioprotective function in certain levels through multiple targets related with NO production, such as eNOS phosphorylation, L-arginine uptake and CAT expression, which may have major clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…Activation of AMPK was found to contribute to elevated [Ca 21 ] i response to hypoxia through activation of store-operated calcium entry. STS has been shown to activate AMPK at the site of Thr(172) in human umbilical vein endothelial cells (60). The roles of ROS, PKC, and AMPK and their relationship to the inhibitory effects of STS on hypoxic up-regulation of TRPC in PASMCs remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AMPK was found to contribute to elevated [Ca 21 ] i response to hypoxia through activation of store-operated calcium entry. STS has been shown to activate AMPK at the site of Thr(172) in human umbilical vein endothelial cells (60). The roles of ROS, PKC, and AMPK and their relationship to the inhibitory effects of STS on hypoxic up-regulation of TRPC in PASMCs remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup of sham and RUPP rats were treated with STS in their drinking water (ϳ27 mg·kg Ϫ1 ·day Ϫ1 ) from the day of surgery to euthanasia. The dosage of STS was chosen following a literature review that determined treatment regimens of 80 mg/day in human (ϳ1.1 mg·kg Ϫ1 ·day Ϫ1 ) (18,19) and ovine (ϳ1.8 mg·kg Ϫ1 ·day Ϫ1 ) (23, 50) trials and a median of 20 mg·kg Ϫ1 ·day Ϫ1 in rodent studies (30,37,45,46,49,51). Systolic and diastolic blood pressures and heart rate were measured by insertion of an in-dwelling carotid catheter under isoflurane anesthesia before euthanasia on GD20.…”
Section: Methodsmentioning
confidence: 99%
“…Our own group has shown STS-induced vasodilation of mesenteric arteries from male Sprague-Dawley rats (21). We demonstrated that STS-induced vasodilation was partially mediated by endothelium-derived hyperpolarization, whereas others have shown effects of STS on NO production, either through direct modulation of eNOS (30) or through nongenomic estrogen receptor actions on eNOS (8). In addition, there have been three clinical studies that have shown positive maternal effects of STS on hypertension in pregnancy: a reduction in morbidity, mean arterial pressure, and blood viscosity, cholesterol, and lipoprotein (20,22,43).…”
mentioning
confidence: 99%
“…In a porcine model of myocardial I/R, MLB increased capillary density and decreased infarct size [51] . In C57 mice, MLB was found to inhibit cardiac hypertrophy and infarction and to improve cardiac function at 4 weeks after induction of the infarction [44] . In rats with left anterior descending coronary artery ligation, MLB treatment effectively improved left ventricle (LV) function and the appearance of the myocardium as compared with a group with acute myocardial infarction (AMI) [52,53] ; MLB treatment also prevented myocardial remodeling, a deleterious consequence of myocardial infarction (MI), by significantly down-regulating the mRNA expression level and activity of MMP-9 [52] .…”
Section: Protecting Against Myocardial Ischemia and Reperfusion (I/r)mentioning
confidence: 93%
“…MLB could also inhibit Ca 2+ influx and decrease NO release in ECs exposed to hypoxia and attenuate cell injury in ECs [43] . In HUVECs, MLB enhanced NO production via the AMPK/ PI3K/Akt pathway [44] . MLB was also found to produce endothelium-dependent vasodilation by regulating NO production through the modulation of heme oxygenase-1 and arginase activities [41] .…”
Section: Preventing Endothelial Dysfunctionmentioning
confidence: 96%